PELATIHAN MOTIVASI KERJA KARYAWAN UNTUK PENINGKATAN KINERJA EKSPOR - Muafi, ' (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
The purpose of this community service is giving knowledge and ability for the employee so that it could increased their work motivation. The material of work motivation is delivered to give intensity, direction, and individual perseverance for the employee to reach the goal of the company. This community service was held in 2 SMEs, which is Raffal Craft and Syifa Handicraft. Both of this SMEs is handicraft SME that is export-oriented and hopefully is able to push and increased export realization of craft industry on Bantul Regency. The method used is giving material within presentation accompanied with simple cases and film screening about work motivation. It is caused by the various education level of the participant, start from Junior High School until Senior High School. Target of this community service is the implementation of community service as expected, which is the increased production of this two SMEs accompanied with improvement quality of the product and good services and also able to compete both in local or global world.